2020
DOI: 10.1128/mra.00746-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Cellulase-Producing Microbulbifer sp. Strain GL-2, Isolated from Marine Fish Intestine

Abstract: Microbulbifer sp. strain GL-2 was isolated from the intestine of a teleost, Girella melanichthys. Here, we report the complete genome sequence of this strain, which produces cellulase(s). Twelve cellulase candidate genes were found on the chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Strain GL-2, the bacterium used in the present study, was isolated from the intestine of a blackfish (Girella melanichthys) (Tanaka et al, 2021). The whole-genome sequence of this strain has been deposited in DDBJ/EMBL/GenBank as Accession Number AP019807 (Sugimoto et al, 2020); a circular map of the genome is shown in Fig. S1.…”
Section: Bacterial Strains and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Strain GL-2, the bacterium used in the present study, was isolated from the intestine of a blackfish (Girella melanichthys) (Tanaka et al, 2021). The whole-genome sequence of this strain has been deposited in DDBJ/EMBL/GenBank as Accession Number AP019807 (Sugimoto et al, 2020); a circular map of the genome is shown in Fig. S1.…”
Section: Bacterial Strains and Culturementioning
confidence: 99%
“…Given that we have previously reported the whole-genome sequence of GL-2 (Sugimoto et al, 2020), we sought, in the present study, to identify and characterize cellulases encoded by this genome, including the expression of the corresponding genes and the enzymatic properties of the resulting recombinant proteins. We report here the cellulase-encoding genes of the GL-2 genome, expression of these genes, and characterization of the encoded enzymes, including the effects of various conditions and saccharides on the expression and activities of these proteins.…”
Section: Introductionmentioning
confidence: 99%